PROGRAMMING EDUCATION IN MAURITIUS: A CRITICAL ANALYSIS OF LOWER SECONDARY CHALLENGES AND STRATEGIES - Rajput, Aisha Fadilah; Choudhury , Ravi Harish; Nair, Leena Krishnan (Research Journal of Health, Medicine and Nursing, 2024)
The realm of programming education encompasses a diverse range of components, including proficiency in programming languages, pseudocode, algorithms, flowcharts, and problem-solving skills. Traditionally, pedagogical approaches in programming have involved establishing foundational knowledge and progressively building complexity to foster effective skill development among students. Central to programming curricula is the cultivation of problem-solving acumen and computational thinking skills. Recognizing the significance of these foundations, the Code Craft project was initiated to bolster the acquisition of fundamental programming skills and understanding of data structures. This report focuses on the unique context of teaching and learning programming at the lower secondary school level in Mauritius, encompassing grades 7 to 9. A notable gap exists in the literature, as no prior studies have investigated the nuances of programming education within this educational stratum. Notably, Mauritius, as revealed by the Survey of ICT and Education in Africa: Mauritius Country Report (2007), introduced Information and Communication Technology (ICT) into secondary schools in 1991. However, its integration faced challenges, particularly in securing a substantive position within the secondary education curriculum, where it was not considered a primary subject until the implementation of the national assessment of education. One impediment to effective programming education in Mauritius was the scarcity of qualified Computer Science educators. Many educators in this domain primarily hailed from information systems or Information Technology backgrounds. Consequently, the lack of specialized educators hindered the seamless integration of programming education into the curriculum. Previous attempts by computer educators to mitigate these challenges yielded suboptimal results, with students failing to achieve satisfactory performance levels. This report aims to fill the existing gap in research by investigating the dynamics of teaching and learning programming at the lower secondary school level in Mauritius. By delving into the historical context, challenges, and strategies employed thus far, the study seeks to contribute valuable insights that can inform the development of effective educational strategies in this domain. As Mauritius grapples with the evolution of ICT education, understanding the specific challenges and opportunities at the lower secondary level is crucial for refining educational approaches and ensuring the successful integration of programming skills into the broader curriculum.